2017
DOI: 10.1038/srep45523
|View full text |Cite
|
Sign up to set email alerts
|

YAP modulates TGF-β1-induced simultaneous apoptosis and EMT through upregulation of the EGF receptor

Abstract: YAP is a transcriptional co-regulator that plays important roles in various patho-physiological processes, including the survival and death of cells. However, the effect of YAP on apoptosis and EMT, simultaneously mediated by TGF-β1, is not known. In this study, we demonstrate that YAP can modulate cell fate of apoptosis versus EMT by acting as a surviving factor. Overexpression of YAP in mouse mammary epithelial (NMuMG) cells suppressed TGF-β1-induced apoptosis, which shifted the cellular response predominant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
58
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 63 publications
(63 citation statements)
references
References 52 publications
5
58
0
Order By: Relevance
“…On the other hand, to initiate tissue repair process, amounts of TGF‐β1 secreted from eosinophil and bronchial epithelial cell increase epithelial vulnerability to allergens and trigger the activation of EMT, which contributes to the subepithelial fibrosis in airway remodelling . Importantly, both of airway epithelial apoptosis and EMT are potently stimulated by TGF‐β, even simultaneously regulated by TGF‐β . Thus, a deeper understanding of TGF‐β1‐induced airway epithelial apoptosis and EMT may provide a new therapeutic asthma treatment in epithelial injury‐repair process.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, to initiate tissue repair process, amounts of TGF‐β1 secreted from eosinophil and bronchial epithelial cell increase epithelial vulnerability to allergens and trigger the activation of EMT, which contributes to the subepithelial fibrosis in airway remodelling . Importantly, both of airway epithelial apoptosis and EMT are potently stimulated by TGF‐β, even simultaneously regulated by TGF‐β . Thus, a deeper understanding of TGF‐β1‐induced airway epithelial apoptosis and EMT may provide a new therapeutic asthma treatment in epithelial injury‐repair process.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, addition of EGF can strongly inhibit TGF-β-induced apoptosis, leading to a significant increase in the portion of cells that underwent EMT [43,47]. In this case, EGF can be mis-regarded as a required factor or co-inducing factor for TGF-β to induce EMT.…”
Section: Tgf-β-induced Concomitant Apoptosis and Emtmentioning
confidence: 99%
“…It has recently been shown that the extent of TGF-β-induced concomitant apoptosis and EMT can be profoundly influenced by YAP and EGF/EGFR signaling [43]. YAP is important for the survival of breast epithelial cells, which can significantly regulate the balance between apoptosis and EMT.…”
Section: The Balance Between Tgf-β-induced Apoptosis and Emt And Itsmentioning
confidence: 99%
See 2 more Smart Citations